Malawi : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues and Statistical Appendix paper analyzes the budget deviations in Malawi, their reasons, and the consequences for the fiscal policy process. It documents the observed deviations of outturn to plan in Malawi, analyzes the reasons for such deviations, outlines some of the consequences, and considers options and actions needed for improvements. The paper evaluates the volatility and predictability of foreign aid inflows and the need for the government to modify its policies, if necessary. The paper also discusses the sources of data used, and evaluates the volatility of total foreign aid and its components.